Neural network study for the subject demand forecasting (2019)
Course planning of an educative center or university is composed of multiple complex problems like the design of the schedule for the students, classrooms, and professors for each signature. One of the problems is the forecasting of the number of subjects to make available for the students; this problem seems easy at first glance because once we have the number of approved and failed students for each subject, we can easily calculate the following demand for each subject. However, there are occasions where the course planning for the following period starts before having the information related to the number of accredited students; which lead us to the problem of forecasting the accreditation ratio for the calculation of the subject demand from the students. In this paper, the performance of a causal model compares to the performance of a statistical model for the forecasting of the approve and fail ratio of the students. The final results show that the causal model outperforms the statistical model for the given instances. We consider that this advantage occurs because the causal model learns the behavior patterns of the training data independently, instead of generalizing the accreditation ratio. Additionally, the statistical method can present significant problems when trying to forecast accreditation ratios for situations that are not found in the training data, while the causal model will use the information learned to predict such situations.